2016
DOI: 10.1021/acs.nanolett.6b00471
|View full text |Cite
|
Sign up to set email alerts
|

Morphology and Phase Controlled Construction of Pt–Ni Nanostructures for Efficient Electrocatalysis

Abstract: Highly open metallic nanoframes represent an emerging class of new nanostructures for advanced catalytic applications due to their fancy outline and largely increased accessible surface area. However, to date, the creation of bimetallic nanoframes with tunable structure remains a challenge. Herein, we develop a simple yet efficient chemical method that allows the preparation of highly composition segregated Pt-Ni nanocrystals with controllable shape and high yield. The selective use of dodecyltrimethylammonium… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
132
0
2

Year Published

2017
2017
2018
2018

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 178 publications
(138 citation statements)
references
References 40 publications
4
132
0
2
Order By: Relevance
“…One approach is to control the surface structure and increase atom utilization efficiency of noble metal NCs in an effort to optimize their catalytic performance while minimizing the usage of noble metal222324252627. The excavated polyhedral NCs, constructed by orderly assembling of ultrathin nanosheets, combine the advantages of both well-defined surfaces and large surface areas, and thus are promising candidates for efficient and low-cost catalysts2829303132.…”
Section: Resultsmentioning
confidence: 99%
“…One approach is to control the surface structure and increase atom utilization efficiency of noble metal NCs in an effort to optimize their catalytic performance while minimizing the usage of noble metal222324252627. The excavated polyhedral NCs, constructed by orderly assembling of ultrathin nanosheets, combine the advantages of both well-defined surfaces and large surface areas, and thus are promising candidates for efficient and low-cost catalysts2829303132.…”
Section: Resultsmentioning
confidence: 99%
“…In recent years, three‐dimensional (3 D) nanoframes (NFs) have been highlighted, because they have many clear advantages, including the fact that they comprise interconnected edges on the nanoscale, offer 3 D accessible surfaces, have a high surface‐to‐volume ratio, and have high atomic utilization . Metallic NFs have emerged as one of the most intriguing catalysts for PEMFCs and have stimulated researchers to develop synthesis methods to obtain Pt‐based NFs with diverse compositions and morphologies . In this regard, highly open 3 D Pt‐based NFs with large accessible surface areas and interconnected edges would be extremely beneficial for the development of high‐performance Pt‐based catalysts towards the oxygen reduction reaction (ORR) and the electrooxidation of small organic molecules .…”
Section: Figurementioning
confidence: 99%
“…[17][18][19][20] Metallic NFs have emerged as one of the most intriguing catalysts for PEMFCsa nd have stimulated researchers to develop synthesis methods to obtain Pt-based NFs with diversec ompositions and morphologies. [21][22][23][24][25] In this regard, highly open 3D Pt-based NFs with large accessible surface areas and interconnected edges would be extremelyb eneficial for the development of high-performance Pt-based catalysts towards the oxygen reduction reaction (ORR) and the electrooxidationo fs mall organic molecules. [26][27][28][29][30] Althoughe stablished Pt-based NFs have been well studied and many experiments as wella st heoretical calculations have shown that NFs can improve the utilization and performance of Pt-based catalysts, precise control of Pt-based NFs with tunable channels has only been scarcely realized but is, nonetheless, critical for any further enhancementi nt he their performance.Herein, we developed an effectives trategy to prepare an ew type of highly composition-segregatedP t-Cu rhombic dodecahedral nanocrystals (RDH NCs).…”
mentioning
confidence: 99%
“…Dendrite and branch structures not only exhibit large surface area and high active sites, but also significantly relieve the aggregation happened in electrocatalytic stability test [9,33,34]. Highly open noble metal nanocages and nanoframes exhibit enhanced electrocatalytic properties due to their three-dimensional accessible surface atoms [20,35,36]. A nanosegregated noble metal skin on these open structures can further improve the catalytic performance [18,37].…”
Section: à2mentioning
confidence: 99%